The role of contact richness in mediated intergroup contact: a test of the contact space framework - Kim, Nuri (2022)
Intergroup contact varies in richness of the experience, yet the effect of contact richness has not been systematically examined. This paper experimentally tested whether and how different levels of mediated contact richness—afforded by different forms of media—affect attitudes toward marginalized outgroups (e.g., refugees, migrant workers). Data collected online from an adult sample (N = 510) found that richness of the mediated contact experience increased feelings of psychological closeness of the depicted outgroup member, which then reduced intergroup anxiety and perceived threat of the outgroup. This, in turn, increased support for policies that promote more humane and equitable conditions for the two outgroups. Theoretical implications for intergroup contact theory and practical implications for utilizing media programs to reduce intergroup bias are discussed.